Ecclesiastical properties as common goods. A challenge for the cultural, social and economic development of local communities (Stato, Chiese e pluralismo confessionale, 2022)
SUMMARY: 1. Introduction - 2. The temporal goods of the Church and the principle of subsidiarity - 3. The notion of common goods in Italy - 4. Some practical cases of ecclesiastical heritage as common goods in Italy- 5. A comparative perspective with Belgium: the strategic plans for the future of churches in Flanders - 6. Future perspectives and conclusions.ABSTRACT: According to recent studies, there are about 600,000 places of worship and several thousands of monasteries and convents in Europe. The process of secularization, the decrease and displacement of the population, the reduction of vocations to the sacred life can be held responsible for the redundancy of the assets of the Catholic Church. These buildings represent an impressive heritage of faith, work and creativity of the communities which made them over the centuries. Most of them are considered as “cultural heritage” by the legislation of the European States, because of their historical, cultural and artistic values. Up to now, the main solution to this phenomenon has consisted in the alienation of these properties. However, the selling and the disposal of these goods by ecclesiastical bodies cannot always be the only and preferable solution. Drawing from the analysis of some case studies in Italy, this paper aims to investigate the role of civil society participation in the regeneration process and the possibility of applying “collaboration pacts” for the management of “common goods”. In the light of the European scope of the phenomenon, a comparison is proposed in line with the legal instrument of “strategic plans”, drawn up by the diocesan bishop and local authorities in Flanders (Belgium).